Herbal Rapid Release Tablets Manufactured from Corchorus Olitorious Leaves - VINOD DOHAREY; NISHA SHARMA (International Journal of Pharma and Bio Sciences, 2010)
Corchorus olitorius (jute) is a native plant of tropical Africa and Asia, and has since spread to Australia, South America and some parts of Europe. Its leafy vegetable is popularly used in soup preparation and folk medicine for the treatment of fever, chronic cystitis, cold and tumors. To overcome the aforementioned disadvantages of traditional dosage forms a solid dosage form i.e. a tablet might be recommended. The first of this study was to formulate and manufacture a rapid release tablet dosage of Corchorus olitorious that would contain an amount of plant material equivalent to that found in its traditional liquid dosage forms and that would meet conventional pharmaceutical standards. A freeze-dried aqueous extract of Corchorus olitorious leaf was prepared and the physical properties of the extract powder were characterized in a preformulation study. Tablets containing 300mg of plant material were then manufactured and tested for uniformity of mass and content, disintegration, dissolution and microbial contamination using Indian Pharmacopoeia methods. The stability of the manufactured tablets under the conditions of 40oC & 75% relative humidity (RH), 25oC & room humidity and 5oC & 0% RH were also evaluated.